Approaches to tax evasion: a bibliometric and mapping analysis of Web of Science indexed studies - Barbu, Liliana; Horobeț, Alexandra; Belașcu, Lucian; Ilie, Anca Gabriela (Journal of Business Economics and Management, 2024)
The primary objective of this study is to uncover and examine the patterns of scientific collaboration within the domain of tax evasion and tax avoidance spanning the years 1975 to 2022. To analyze the dissemination of knowledge on a worldwide scale, we investigated the interconnections among authors, journals, countries, and institutions. A total of 1456 publications were retrieved from the Web of Science repository. Bibliographic analysis and network visualization were conducted using CiteSpace. The publications analysed in this study consisted of 1,456 articles authored by 2478 scholars affiliated with 1355 institutions. The publications were distributed among 724 distinct journals and originated from 98 countries. The United States of America is found to be the most productive nation, with McGee, R.W. being recognised as the most prolific author. The League of European Research Universities is recognised as the most productive institution, whereas the Journal of Public Economics is identified as the most productive publication. The findings show that authors who exhibit high levels of productivity also tend to demonstrate a strong inclination toward collaboration. Furthermore, the findings reveal that the interest of the scholars in particular topics in this research has evolved over time.